The Impact of Nagari Expansion on the Use of Village-Nagari Fund Allocations for Development in Nagari Ladang Panjang, Pasaman Regency - Hamidah, Siti; Malau, Hasbullah (The Future of Education Journal, 2025)
The expansion of villages is also part of an effort to improve the ability of village governments to shorten the span of government control so as to increase the effectiveness of government administration and development management. The main objective of village expansion is to increase the effectiveness and efficiency of government administration, as well as to increase community participation in government, one of which is to increase village development. This study aims to analyze the impact of village expansion on the use of Village-Nagari Fund Allocation on development and identify factors that influence changes in fund allocation after expansion. The method used in this study is a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation studies involving the village government, the Village Consultative Body (BAMUS), and the local community. The results of the study indicate that village expansion has reduced the receipt of Village-Nagari Fund Allocation in Ladang Panjang Village, which has an impact on the limited use of the Village-Nagari Fund Allocation budget for infrastructure development and public services. This expansion also affects the effectiveness of village financial management, where several development projects cannot be realized due to budget constraints. Factors that influence changes in village fund allocation include changes in population, administrative area, and fund distribution policies from local governments.